Characterization of Pictorial Materials of Two 18th Century Sculptures: King David and Bathsheba - Francis A. C. R. A. Sanches; Raysa C. Nardes; Ramon S. dos Santos; Roberta G. Leitão; Catarine C. G. Leitão; Joaquim T. Assis; Elanie T. de Gusmão; Ricardo T. Lopes; Davi F. de Oliveira; Marcelino J. dos Anjos (Semina: Ciências Exatas e Tecnológicas, 2023)
In this {work}, the X-ray fluorescence technique was employed to characterize the pictorial materials used in two sculptures from the 18th. In addition, Raman spectroscopy was used to characterize the preparation layers used in the sculptures. The analyzed sculptures are carved in wood, with gilding and polychrome, and represent the biblical characters, Bathsheba, and King David. The sculptures are property of the Church of Nossa Senhora do Pilar, in Duque de Caxias, RJ. XRF {analyzes} were performed using a portable ED-XRF system, which has a low-power X-ray tube (Amptek) with a silver target (Ag) and an SDD detector (Amptek). Raman spectroscopy {analyzes} were performed using the DXR2 Raman microscopy equipment (Thermo Fisher Scientific) with a 785 nm laser source. The results obtained from the XRF and Raman spectroscopy techniques suggest the presence of Gypsum, Calcite, Calcium Sulfate. In addition, the results obtained suggest the presence of the following pigments in the sculptures: Lead white, Titanium White, Lithopone, Ochre, Vermilion, Red Lead and gilding with gold leaf. The studies also showed that the Bathsheba sculpture was probably subjected to some processes of chromatic reintegration over the years due to the heterogeneity of pigments found in the same region